Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan Pada Maskapai Lion Air di Bandar Udara Internasional El Tari Kupang - Gerda Marselina Andriyani Odem; Esti Nur Wakhidah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Lion Air is one of many other airlines operating at El Tari International Airport in Kupang. This airline is in great demand by people in the city of Kupang because the fares are quite low and affordable for people from the middle class. This research aims to determine how much influence the quality of service (tangibles, reliability, responsiveness, assurance, empathy) has on customer loyalty. This study uses a quantitative approach with data collection carried out on 5 – 30 October 2021 by distributing questionnaires to Lion Air customers. Analysis of the data method used using Multiple Linear Regression Analysis with the aim of knowing the effect of one or more independent variables on the dependent variable. This research was conducted by distributing a survey to 100 customers who have used the services of Lion Air at El Tari Kupang International Airport. The results of the study show that (1) the tangibles variable is not significantly related to customer loyalty, (2) reliability is significantly related to customer loyalty, (3) responsiveness is not significantly related to customer loyalty, (4) assurance is not significantly related on customer loyalty, (5) empathy has a significant effect on customer loyalty, (6) simultaneously significant values ​​of tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4) empathy (X5) variables affect customer satisfaction (Y) is 0.00 < 0.05 and the calculated F value is 19.625 > F table 2.31, so together or simultaneously have a significant effect on customer loyalty. Keywords: Service Quality, Customer Loyalty